Arab Tribalism, Traditionalism and its Implications during the Early Annals of Islamic Polity (Khairulummah, 2023)
In all human civilisations, there is the concept of prejudice, which is one of the requirements for the survival of a society. One trait of the pre-Islamic Arabs that persisted fundamentally among the Arabs even after Islam is prejudice. Prejudice, which was pervasive among pre-Islamic Arabs, was crucial to post-Islamic Arab developments as well as to the happenings inside the Islamic world. The contribution made by the Arab tribes to the spread of Islam, the strengthening of Dar al-Islam [House of Islam], as well as in the Umayyad dynasty's reign and governance. Each confederation of tribes spearheaded the spread of Islam in a distinct direction, with the Bani Mudhar leading the way towards the east and the Bani Qahtan leading the way towards the west, due to the historical rivalry between the two groups. Tribal disputes were a means by which the Umayyads kept their hold on power; nevertheless, the Abbasids skillfully employed this strategy to establish a new dynasty. Muslim authors like Ibn Khaldun and Al-Maqrizi have discussed these divisions, highlighting their importance in the expansion of Islamic Empire. Arab tribes played a significant role in conquering territories, forming the first Muslim dynasty, and controlling power through tribal disputes. Tribal rivalry was a tactic employed by the Abbasids and Umayyads to share power; this was also the reason behind the Umayyads' downfall and the inception of the Abbasid revolt. This research aims to investigate the bias inside the Arab tribal system and its fallout and implications.
Keywords: tribes, Bani Qahtan, Bani Mudhar, Marwanids, Abbasids